Identification of serum biomarker panel to differentiate malignant from benign thyroid nodules using multiplex bead assay - Ragaa Abdelkader Ramadan; Wafaa Ragab; Ramy Samir Assaad; Ahmed Elsayed Shaaban; Amira Ibrahim Fayad (Journal of the Egyptian National Cancer Institute, 2020)
Abstract Background The challenging target in the workup of thyroid nodule(s) is to exclude or diagnose thyroid cancer efficiently prior to surgical intervention. The present work studied a panel of eight serum biomarkers to differentiate benign from malignant thyroid nodules, aiming at reducing unnecessary thyroidectomy performed for inconclusive preoperative fine needle aspiration cytology. Serum interleukin-5 (IL-5), interleukin-8 (IL-8), hepatocyte growth factor (HGF), epidermal growth factor (EGF), angiopietin (Ang1), nonokine induced by interferon gamma (MIG), galectin (Gal-3), and vitamin D-binding protein (VDRP) were quantified by multiplex bead assay using Luminex xMAP technology. The study was conducted on 60 subjects of three groups (20 each; healthy controls, benign thyroid nodule, and malignant thyroid nodule). Results Significant increase of the following biomarkers in the malignant group compared to the benign group was found; IL-8: 29.7 vs 8.75 pg/ml, p < 0.001, EGF: 128.7 vs 6.72 pg/ml, p < 0.001, HGF: 173.2 vs 112.2 pg/ml, p = 0.012, MIG: 776.7 vs 438 pg/ml, p = 0.023, and Ang-1: 95016 vs 33327.5 pg/ml, p = 0.014. No significant differences were detected for IL-5, Gal-3, and VDBP. Serum IL-8 and EGF showed the highest diagnostic performance individually with area under the curve (AUC) 0.849 and 0.848, respectively. The combined biomarker panels of IL-8 and EGF and IL-8, EGF, and MIG have reached a sensitivity and specificity of 95% and 65%, respectively, with a negative predictive value of 92.9%. Conclusions Serum IL-8 and EGF individually or the combined biomarker panel of IL-8, EGF, and MIG are promising tests that can help to exclude malignancy in thyroid nodule workup.